2021
DOI: 10.3389/fonc.2020.594141
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Phenotype-Based Screen Identifies Therapeutic Agents Selective for Metastatic Prostate Cancer

Abstract: In American men, prostate cancer is the second leading cause of cancer-related death. Dissemination of prostate cancer cells to distant organs significantly worsens patients’ prognosis, and currently there are no effective treatment options that can cure advanced-stage prostate cancer. In an effort to identify compounds selective for metastatic prostate cancer cells over benign prostate cancer cells or normal prostate epithelial cells, we applied a phenotype-based in vitro drug screening method utilizing multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…In recent years, more systematic and precise screening and treatment have significantly improved the prognosis of PC up to a point[ 21 , 22 ]. However, effective treatment of PCLM still faces significant challenges and requires further exploration and breakthroughs[ 23 ]. Moreover, the number of PCLM patients is very large globally[ 1 , 2 , 4 ], which is further driving the exploration of and research into PCLM by scholars worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more systematic and precise screening and treatment have significantly improved the prognosis of PC up to a point[ 21 , 22 ]. However, effective treatment of PCLM still faces significant challenges and requires further exploration and breakthroughs[ 23 ]. Moreover, the number of PCLM patients is very large globally[ 1 , 2 , 4 ], which is further driving the exploration of and research into PCLM by scholars worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…ABZ is a Food and Drug Administration (FDA)-approved broad-spectrum anthelmintic with low toxicity and is widely used in humans and animals 11 . Recently, ABZ has been reported to induce antitumor activities in various cancer types 12 14 . Moreover, several studies demonstrated that other benzimidazole anthelmintics (fenbendazole, flubendazole, and mebendazole) also induce anti-leukemic activities 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 20% of the remaining patients with intermediate to high risk disease ultimately progress to aggressive metastatic forms of PCa which is incurable, and with a survival rate of 30%. [2][3][4][5][6] In clinical practice, currently two glycoproteins, prostate specific antigen (PSA) and prostate-specific membrane antigen (PSMA) are frequently used for the diagnosis of prostate cancer. PSA has limitations, and in 2012 the US Preventive Services Task Force recommended against the utilization PSA-based tests for screening the disease 7 based on low sensitivity and specificity as a biomarker.…”
Section: Introductionmentioning
confidence: 99%